The Transformers’ Significance in the Topical Argentine (Anclajes, 2011)
Roberto Arlt's first novel Mad Toy (1926) inaugurated a new genealogy in Argentine literature at the beginning of the Twentieth Century. Such a period was characterized by an exultant aesthetics and a purely urban narrative. The contemporary writing dynamics has introduced different sort of imagery that makes technique ─provided by mass media and popular culture─ the configurative element of the narrative perception.  The new paradigm developed by Donna Haraway ─the notion of cyborg─ grants access to a new theoretical approach to the Transformers’ image. The Bicentennial celebration has reinforced the vitality and novelistic potential of the Argentine literature, inherited from adventure and periodical novels but, at the same time, cross-grained by a more violent and parody-like aesthetics. This piece of article explores a series of elements which have been intensified as a result of a new manhood conception in two recent novels, Félix Bruzzone’s Los Topos (2008) and Mariano García’s Letra Muerta (2009).
Keywords: argentine literature; cyborg; manhood; mass culture